Comparison between different first-line therapy protocols in eradicating Helicobacter pylori in a region with high clarithromycin resistance - Yilmaz, Baris; Koseoglu, Huseyin; Coskun, Yusuf; Deveci, Murat; Kekilli, Murat (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
Introduction : Helicobacter pylori infection is encountered in more than 50% of the world population. A high rate of clarithromycin resistance is observed among Helicobacter pylori strains in some regions because clarithromycin is a drug commonly used for the treatment of other infections. Aim : To identify an efficient eradication protocol for patients infected with H. pylorii and to suggest an alternative first-line therapy particularly in countries with high clarithromycin resistance. Material and methods : Patients (18–75 years old) having dyspeptic complaints in a 1-year period and diagnosed with H. pylorii infection by gastric biopsy were included and randomised to three groups, each receiving different sequential eradication therapy (LAM-B: lansoprazole, amoxicillin, metronidazole, bismuth: LAM-T: lansoprazole, amoxicillin, metronidazole, tetracycline; LAM-BT: lansoprazole, amoxicillin, metronidazole, bismuth, tetracycline). Eradication was evaluated via urea breath test. Results : This study included 166 patients (mean age: 40 ±12 years; female, 68.7%) with H. pylorii infection. Among them, 50 (30.1%) were in the LAM-B group, 59 (35.5%) were in the LAM-T group, and 57 (34.3%) were in the LAM-BT group. The non-steroidal anti-inflammatory drug use was the lowest in the LAM-BT group. Eradication rates were over 80% and similar in each group, with the highest rate in the LAM-BT group (93%). Adverse event rate was the highest in the LAM-T group. Helicobacter pylori eradication was achieved in 143 (86.1%) patients. Conclusions : The combination regimens without clarithromycin achieved an eradication rate over 80% in all groups. Knowing and monitoring the regional antibiotic resistance rates is important for successful treatment of H. pylorii infections.